Relationships between maladaptive cognitive emotion regulation strategies and psychopathology in adolescents from Bangladesh - Nadia Garnefski; Samiul Hossain; Vivian Kraaij (Archives of Depression and Anxiety - Peertechz Publications, 2017)
Introduction: Psychopathology   of   adolescents   in   developing   countries   such   as   Bangladesh   is a  neglected  problem,  which  should  get  more  attention,  especially  with  a  focus  on finding  targets for prevention  and  intervention.  Aim  of  the  study  was  to  study  relationships  between  cognitive  emotion regulation strategies and psychopathology in Bengali adolescents. Methods: The sample consisted of 340 12-to-18-year old adolescents from Bangladesh. The Cognitive Emotion Regulation Questionnaire (CERQ) was used to measure cognitive emotion regulation strategies. The  SCL-90  was  used  to  measure  symptoms  of  depression,  anxiety  and  hostility.  Relationships  between CERQ and SCL-90 scales were studied by Multiple Regression Analysis. Results: With   regard   to   relationships   between   CERQ   strategies   and   psychopathology:   Higher extents  of  'Worry-focused'  cognitive  styles  appeared  to  be  related  to  the  reporting  of  more  symptoms of  psychopathology,  while  more  'Reappraisal-focused'  styles  were  associated  with  the  reporting  of  less symptoms of psychopathology. Discussion: The  results  with  regard  to  the  relationships  between  cognitive  emotion  regulation strategies and psychopathology may provide possible targets for interventions to improve mental health in adolescents in developing countries.